Optimization of agile-supported project management using a multi-criteria approach - Gafarov, J. (Національний технічний університет "Харківський політехнічний інститут", 2026)
In modern project environments characterized by uncertainty and frequent change, organizations face increasing challenges in selecting effective project management methodologies. Although Agile approaches are widely recognized for their flexibility and adaptability, their actual contribution to project success is not always clear, particularly in hybrid and non-IT organizational contexts. This study focuses on the evaluation and optimization of Agile-supported project management using a structured multi-criteria approach.
Keywords: optimization; project management; multi-criteria approach; decision-making; scientific Innovation; management methodologies